Kontribusi Penentuan Nasib Sendiri Untuk Mendorong Prestasi Akademik Siswa Dalam Pembelajaran Online - Krisnita Candrawati (Program Studi Manajemen Pendidikan, 2024)
The aim of this study is to examines the role of self-determination in encouraging student academic performance through online learning. Using TTF framewor, this study uses a quantitative approach with path analysis. The population used is Yogyakarta students while the sample used is 162 students. Analysis using partial regression analysis (Partial Least Square-Structural Equation Model (PLS-SEM). The software used is smartPLS 3.0. The results showed that there is a mediating role of user satisfaction in the influence of student self determination on academic performance. This research shows that self-determination is a variable that higher education managers should consider when implementing online learning. This research adds a self-determination variable to the TTF framework. This is based on the phenomenon of minimal participation in online learning. This research also confirms the TTF framework on performance which has never been studied in a higher education setting. The implications of this research underscore the importance of SD as a component in online learning that higher education managers should pay attention to. The results of this study explain that SD effects AP through student satisfaction in participating in online learning